Impact of Educational Leadership on Teacher Performance: A Case of Public Primary Schools in Asem Circuit of Kumas Metropolis - Appiah Otabil, Francis (KNUST, 2026)
A thesis submitted to the Department of Educational Innovations in Science and Technology, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the degree of MASTER OF PHILOSOPHY IN ART EDUCATION